The Neorealist City: Territory, Iconography and Maps of Rome in Bicycle Thieves - Colella, Federico (Bitacora Arquitectura, 2019)
The neorealist city corresponds to the vision of certain Italian directors from the 1940s to the 1960s who explored the changing urban space of Rome. This article analyzes Bicycle Thieves, a 1948 film by Vittorio De Sica. A cartographic analysis of the locations chosen by the director allows for the creation of a new symbolic map of the Italian capital that explores its urban periphery, which had never been depicted in film before, thus laying the groundwork for contemporary representations of the everyday landscapes and phenomena of the city